Impact of injection scheduling on CO2 migration and trapping efficiency in the Johansen formation - Hai T. Nguyen (PLoS ONE, 2025)
Injection scheduling is increasingly considered as an operational lever for optimizing carbon dioxide (CO 2 ) storage in saline aquifers, yet its long-term impact on trapping efficiency at field scale remains uncertain. This study employs a field-calibrated vertical equilibrium model of the Johansen formation, offshore Norway, to compare four injection strategies: constant, ramped, pulsed, and low steady, under equal total injected mass. Simulations span 1000 years, including both injection and post-injection phases, to evaluate plume migration, bottom hole pressure (BHP) evolution, and partitioning among residual and solubility trapping. Results show that while injection schedule significantly influences short-term injectivity and peak BHP with differences up to 80 bar, its effect on millennial-scale trapping efficiency is negligible. By 1000 years, all scenarios converge to a similar distribution, with 57–58% dissolved in brine, 30–34% immobilized by residual trapping, and 8–9% persisting as a mobile plume, with inter-schedule differences less than 2% of the total injected mass. These findings indicate that, in a laterally open and well-connected aquifer such as Johansen, long-term storage security is governed primarily by reservoir properties and dissolution dynamics rather than by operational schedule. Consequently, injection scheduling should be regarded as a tool for short-term pressure management and infrastructure safety, not as a determinant of ultimate storage performance. This distinction provides practical guidance for designing CO 2 storage projects and regulatory assessments of long-term containment.